Equal opportunities, fair work and social protection: Impacts of COVID-19 on young people in Portuguese rural territories - Simões, F.; Carmo, R. M.; Fernandes, B. (Public policies for territorial cohesion, 2023)
Several international organizations, as well as worldwide scholarship, have abundantly shown that young people under 34 are among the groups struggling the most with COVID-19 economic and social impacts. Seldom, however, does scholarship focus on the uneven effects of the pandemic on younger generations across different types of territories. Overall, young people in rural territories tend to face much greater adversities. These territories concentrate less population, show strong ageing trends trend and depict a lower settlement rate. Rural younger generations struggle to strive, because rural areas depend heavily on declining economic activities such as farming, are plagued by precarious jobs, and display limited institutional support compared to (sub)urban areas. In Portugal, the country’s population is unevenly distributed between affluent, high-density coastal areas and inlands and archipelagos with a considerable rural predominance. The COVID-19 crisis has the potential to further stretch the existing inequalities among young people due to spatial distribution. Therefore, in this chapter, we discuss the impact of the recent pandemic crisis on rural Portuguese young people. We will do so by characterizing headline indicators in the three domains of the European Pillar of Social Rights, namely equal opportunities (e.g., Early School Leavers from Education and Training), fair working conditions (e.g., Youth Unemployment), and social protection and inclusion (e.g., at risk of poverty and social exclusion). We expect to reach an initial comprehension of the challenges faced by rural Portuguese young people in the aftermath of the COVID-19 crisis in three domains: education, employment and social inclusion. We also discuss how more nuanced territorial conceptualizations (e.g., low-density areas) and policymaking can add alternative views about young people’s living conditions due to subnational disparities.